The Threshold Induction Temperature of the 90-kDa Heat Shock Protein is Subject to Acclimatization in Eurythermal Goby Fishes (Genus Gillichthys) - Dietz, Thomas J.; Somero, George N. (Proceedings of the National Academy of Sciences - PNAS, 1992)
Two extremely eurythermal goby fishes, Gillichthys mirabilis and Gillichthys seta, which encounter habitat temperature variations of ≈30⚬C, showed seasonal acclimatization of endogenous levels and of onset temperatures for enhanced synthesis of a 90-kDa-class heat shock protein (HSP90). Summer-acclimatized fishes had higher levels of HSP90 in brain tissue than winter-acclimatized specimens, as shown by Western blot analysis. For winter-acclimatized fishes, increased synthesis of HSP90 was observed when the temperature was raised from a control temperature (18⚬C) to 28⚬C. For summer-acclimatized fish, no significantly increased synthesis of HSP90 occurred until the experimental temperature was raised to 32⚬C. These data suggest that the threshold temperature at which enhanced expression of HSP-encoding genes occurs is not hard-wired genetically but may be subject to acclimatization. A causal relationship between seasonal changes in steady-state levels of HSP90 and the threshold temperature for enhanced HSP90 synthesis is discussed in terms of existing models for the regulation of HSP gene expression.